Approaches to internet pragmatics theory and practice - Xie, Chaoqun; Yus, Francisco; Haberland, Hartmut (Pragmatics & beyond new series (P&BNS),, 2021)
"Internet-mediated communication is pervasive nowadays, in an age in which many people shy away from physical settings and often rely, instead, on social media and messaging apps for their everyday communicative needs. Since pragmatics deals with communication in context and how more gets communicated than is said (or typed), applications of this linguistic perspective to internet communication, under the umbrella label of internet pragmatics, are not only welcome, but necessary. The volume covers straightforward applications of pragmatic phenomena to internet interactions, as happens with speech acts and contextualization, and internet-specific kinds of communication such as the one taking place on WhatsApp, WeChat and Twitter. This collection also addresses the role of emoticons and emoji in typed-text dialogues and the importance of "physical place" in internet interactions (exhibiting an interplay of online-offline environments), as is the case in the role of place in locative media and in broader place-related communication, as in migration"--